(untitled) (Journal of Population and Development, 2022)
This study attempts to analyze the trend in maternal health care utilization: antenatal care, delivery care, and postnatal care in Nepal. Maternal health remains a major challenge in developing countries despite improvements in medical technology and several efforts to improve maternal health care services. This study is based on Nepal Demographic and Health Survey data from 2006, 2011, and 2016. It covers 4,066 women in 2006, 4,148 in 2011 and 3,998 in 2016 for antenatal care. In the study, this analysis is confined to women aged (15-49) who had a live birth in the five years preceding the survey. Data on delivery care were obtained for all births that occurred in the five or two years preceding the survey. This study comprises 2030 women in 2011 and 1,978 women in 2016 aged 15–49 years who had a live birth in the two years preceding the survey on childbirth, and postnatal care. Especially, the study deals with antenatal, delivery care, and postnatal care. There is a substantial increase in the utilization of antenatal care (ANC) by skilled health providers from, 44 percent in 2006 to 84 percent in 2016 respectively. Still, six percent percentage do not seek even one-time ANC care and the percentage of women who seek 4 or more ANC care from a skilled service provider is low. Still, two fifth percent of delivery take place at home. postnatal service is still very low in Nepal. This study’s results suggest the need for efforts to be addressed to improve the use of maternal health care services in Nepal. There is a need to increase the use of postnatal checkup as well as delivery assisted by skilled attendants.